Secret of the Tower - Doyle, Debra, 1952-; Macdonald, James, 1954-; Mitchell, Judith, 1951- (Mahwah, N.J. : Troll Associates, 1990)
Determined to become a wizard, twelve-year-old Randal is delighted to be accepted into the famed School of Wizardry, but his apprenticeship is marred when he realizes that one of the master wizards is using evil spells to destroy the school and gain supreme power.
G6
Keywords: Wizards -- Fiction; Knights and knighthood -- Fiction; Adventure and adventurers -- Fiction